Case report: A challenging case of mixed-variant myofibroblastoma with complex imaging and pathological diagnosis - Kawasaki, Tomonori; Ichikawa, Jiro; Kanno, Satoshi; Onohara, Kojiro; Wako, Masanori; Tatsuno, Rikito; Ochiai, Satoshi; Watanabe, Takuya; Torigoe, Tomoaki (Frontiers in Oncology, 2024)
Myofibroblastomas are benign mesenchymal tumors that frequently occur in the groin. They show variable morphology, and the differential histopathological diagnoses are broad, including lipomatous to myxoid tumors. In addition, both pathological and imaging findings may be complex, which makes diagnosis challenging. We herein present a case of a mixed-variant myofibroblastoma of the wrist in a 73-year-old woman. Considering the long clinical course of more than 20 years and the imaging findings, a benign myxoid tumor including a schwannoma was suspected; however, the histopathological findings from resected specimens suggested a diagnosis of myxofibrosarcoma. Additional histopathological findings led to a diagnosis of mixed-variant myofibroblastoma. The differential diagnosis of myofibroblastoma extends beyond imaging to pathological findings because of the number of possible variants. This case reinforces the notion that the gold standard treatment for soft tissue tumors is to perform surgery only after determining the correct diagnosis by biopsy.